Cluster-Like Headache Secondary to Anamnesis of Sphenoid Ridge Meningioma: A Case Report and Literature Review - Kou, Liang; Huang, Jinsha; Xu, Yan; Han, Chao; Ma, Kai; Guo, Xingfang; Xia, Yun; Wan, Fang; Yin, Sijia; Hu, Junjie; Wu, Jiawei; Sun, Yadi; et al. (Frontiers in Neurology, 2019)
Cluster headache is generally considered to be a primary headache; secondary cluster-like headache is quite rare, while cluster-like headache secondary to meningioma is even rarer. Here, we describe an unusual case with cluster-like headache 2.5 years after sphenoid ridge meningioma surgery. The cluster-like headache and meningioma were on the same side, and even at the same position. Furthermore, the cluster-like headache lasted for 6 months. In addition, the patient did not respond well to conventional treatments for cluster headache, such as oxygen inhalation, carbamazepine, and tramadol. Brain magnetic resonance imaging demonstrated a softening lesion, glial hyperplasia, and localized thickening and enhancement of the dura in the left frontal-temporal lobe. However, positron-emission computed tomography showed reduced metabolism in the left frontal-temporal lobe. Although the possibility of a primary headache cannot be completely eliminated, the association between cluster-like headache and probable tumor recurrence or postoperative changes should be considered.